2020
DOI: 10.1146/annurev-bioeng-082219-033358
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Aided Design of Microfluidic Circuits

Abstract: Microfluidic devices developed over the past decade feature greater intricacy, increased performance requirements, new materials, and innovative fabrication methods. Consequentially, new algorithmic and design approaches have been developed to introduce optimization and computer-aided design to microfluidic circuits: from conceptualization to specification, synthesis, realization, and refinement. The field includes the development of new description languages, optimization methods, benchmarks, and integrated d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 108 publications
0
18
0
Order By: Relevance
“…On the other hand, at temperatures above 125 °C, the paper substrate suffered degradation over time. Zhong et al found out that, for temperatures above 150 °C, the paper curled up, and the color of the paper changed [50]. Additionally, the barriers were not fully homogeneous from device to device, obtaining that more than 60% of the devices were not operative.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, at temperatures above 125 °C, the paper substrate suffered degradation over time. Zhong et al found out that, for temperatures above 150 °C, the paper curled up, and the color of the paper changed [50]. Additionally, the barriers were not fully homogeneous from device to device, obtaining that more than 60% of the devices were not operative.…”
Section: Resultsmentioning
confidence: 99%
“…The design of paper-based devices is generally made by ordinary designing software, such as AutoCAD or Adobe Illustrator. However, specific software has been developed for the selection of the shape, width of the barrier and width of the channel [14,50,51]. In particular, during the patterning process of the paper substrate, it is important to be able to obtain the desired dimensions of the wax barriers with well-controlled and uniform features in the final printed and heated device.…”
Section: Introductionmentioning
confidence: 99%
“…AI requires appropriate training datasets and algorithms to improve results before testing, similar to traditional statistical methods [ 213 , 214 , 215 , 216 , 217 ]. AI focuses on building automated decision systems, unlike traditional statistical approaches that rely on rule-based systems [ 215 , 218 ]. AI methods are categorized into three types of learning techniques: supervised, unsupervised, or semi-supervised or augmented learning.…”
Section: The Future Of Microfluidicsmentioning
confidence: 99%
“…Sequence-based AI approaches can be used for selection and testing in a wet-lab experiment to refine the design of therapeutic peptides before they are synthesized. This complicates their usefulness to the end-user and highlights the need to systematically evaluate and develop these approaches, taking into account the state of the art in methodology and predictive performance [ 216 , 218 ].…”
Section: The Future Of Microfluidicsmentioning
confidence: 99%
“…This can be attributed to the phenomenological complexity of droplet formation 16,17 , lack of predictive understanding [18][19][20] , high fabrication cost inherent to photolithography 21 , and unreliability of numerical simulations to capture the intricate dynamics of multiphase flows 20 . Consequently, expertise and an iterative design process is required to achieve the desired performance 22,23 . Several geometries including T-junction 7 , step-emulsification 24 , co-flow 25 , and flow-focusing 26 can be used to generate droplets.…”
mentioning
confidence: 99%